Strength-Endurance Training Reduces the Hamstrings Strength Decline Following Simulated Football Competition in Female Players - Delextrat, Anne; Piquet, Jessica; Matthews, Martyn J.; Cohen, Daniel D. (Frontiers in Physiology, 2018)
Hamstring strains are the most common injury in multiple sprint sports, with inadequate eccentric hamstring strength and fatigue identified as important risk factors. Resistance training interventions aimed at reducing injury risk typically focus on the development of maximum strength, while little is known about the impact of training on hamstring fatigue resistance. The present study compared the effects of strength-endurance (SE) with a strength intervention (S) on the eccentric hamstring strength decline induced by a simulated soccer match. Twenty-one female soccer players were randomly assigned to a S group (n=10) or a SE group (n=11). Hamstrings and quadriceps isokinetic concentric and eccentric peak torque (PT) were assessed at 120º.s-1 and hamstrings-to-quadriceps ratio (HEcc:QCon) calculated, pre- and immediately post a 90-min simulated match (BEAST90). This was repeated following a 7-week intervention of either 3-5 sets of 6RM leg curl and stiff-leg deadlift with 3-mins inter-set rest (S), or the same exercises performed using three sets of 12-20 RM with 45-90s inter-set rest (SE). At baseline, the simulated match led to significant declines in hamstrings eccentric peak torque (EccPT) in both groups in both dominant (D) and non-dominant (ND) legs (SE: D;-15.5, ND; -15.6%, P=0.001 to 0.016; S: D;-12.3%, ND; -15.5%, P=0.001 to 0.018). After the 7 week intervention, we observed a group*intervention*match interaction such that there was no significant decline in EccPT in the SE group following the simulated match (D; 5.3% ND; 2.0%), but there remained significant declines in the S group (D;-14.2%. ND; -15.5%, P=0.018 to P=0.001). Similarly, in the SE group, there was a significant decrease in the HEcc:QCon in D before (-14.2%, P=0.007), but not after the training intervention, whereas declines were observed in the S group both at baseline, and following the intervention (D; -13.9% ND;-15.6%, P=0.045). These results demonstrate that SE training can reduce the magnitude of the eccentric peak torque decline observed during soccer competition. As inadequate eccentric strength and fatigue are both risk factors for hamstring injury, SE training should be considered along with the development of peak eccentric strength, as a component of programs aimed at reducing injury risk in multiple-sprint sports.